Penelope Heynes Turning at 100 m of Her World-record 200 m Race at the 1999 Pan Pacific Championships in Sydney - Rushall, B. S.
Video pictures (44 frames) and the appropriate technical/ biomechanical explanations for Penelope Heynes Turning at 100 m of Her World-record 200 m Race at the 1999 Pan Pacific Championships in Sydney. This turn is similar to that executed at the 150-m mark. After a complete stroke upon approaching the wall, Penelope Heynes executes a quick arm pull without kick.